PENERAPAN PRINSIP MENGENALI PENGGUNA JASA OLEH NOTARIS SEBAGAI PIHAK PELAPOR TINDAK PIDANA PENCUCIAN UANG YANG MEMILIKI KEWAJIBAN MENJAGA KERAHASIAAN AKTA BERDASARKAN UNDANG-UNDANG JABATAN NOTARIS - ELISABETH ELISABETH (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Budiman Ginting, SH, MHum2. Notaris Dr. Suprayitno, SH, MKn3. Dr. T. Keizerina Devi A, SH, CN, MHum The establishment of the principle of recognizing a service owner began with the issuance of Government Regulation No. 43/2015 on Notary’s Obligation to be an informer in TPPU (Money Laundering Criminal Act). This is because Notary’s service is vulnerable to concealing the origin of property which comes from criminal act. The research was about the conflicting norms regulated in Article 16, paragraph 1, letter f of UUJN (Notarial Act) on Notary’s Liability for the confidentiality of deeds and as an informer of TPPU is responsible to apply PMPJ (Principle of Recognizing Service Users) according to the Ministerial Decree No. 9/2017. The objective of the research was why it was necessary to apply PMPJ, how about a Notary’s liability to keep the confidentiality of deeds, and how the Notaries in Medan implement PMPJ.The result of the research shows that in playing his role in social ultimate goal to detect the use of a notary’s service by TPPU perpetrators, a Notary is liable to implement PMPJ.Keywords: Principle of Recognizing Service Users, Money Laundering Criminal Act, Notary, Informer